The impact of minimum wages on income inequality in the EU - Stefano Filauro; Klaus Grünberger; Edlira Narazani (European Commission, Joint Research Centre (JRC), 2023)
A number of studies documents that minimum wage policies have the potential to reduce income inequality. The recently adopted EU Commission's proposal for a Directive on adequate minimum wages was supported by a detailed analysis of the social impacts of hypothetical minimum wage levels in countries with a statutory minimum wage. This paper extends these country-level analyses by exploring the impact of minimum wage policies on EU-level income inequality. To our knowledge, this is the first study that uses a microsimulation model such as EUROMOD to assess the impact of EU-promoted policies on the distribution of income in the EU, beyond their national effects. Assuming no employment effects, static simulation results show that a hypothetical minimum wage corresponding to 60% of the national median wage would bring about a small but significant reduction in EU-level disposable income inequality (by 0.75% in 2019 as measured through the Gini index). This result stems primarily from a reduction in the within-country component of income inequality as the effect on inequality between countries is rather muted. The reduction in EU-level income inequality is the highest in disposable incomes, but some reduction is detectable also in market incomes. In turn, the withdrawal of social benefits because of higher minimum wages seems to neutralise part of this inequality reduction.
Keywords: H31; I32; J31; 330; Minimum wage; Microsimulation; European Union; Income inequality; EUROMOD